PENGARUH KOMPETENSI SUMBER DAYA MANUSIA, LITERASI KEUANGAN, MODAL KEUANGAN, DAN MODAL SOSIAL TERHADAP KINERJA UMKM - Nur'aini Rokhmania; Hisbiyah Maulatuzulfa (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
In Indonesia, MSMEs have an important role in the economic sector which is expected to improve the country's economy. MSMEs are a wide choice of job providers in various fields that can reduce the number of existing unemployed. Sidoarjo Regency which is dubbed as the city of MSMEs has hundreds of thousands of MSMEs in various fields. Based on data from the Department of Cooperatives and SMEs of East Java Province, from 2016 to 2018 cooperatives and SMEs in East Java contributed more than 56% to GRDP. The purpose of this study was to examine the effect of human resource competence, financial literacy including debt management literacy and budgeting literacy, financial capital, and social capital on MSME performance. The population of this research is Sidoarjo Regency with the sampling technique using purposive sampling. The number of samples in this study were 110 SMEs. The data analysis technique used is SEM-PLS using the WarpPLS 7.0 application. The results of this study indicate that the variables of human resource competence, debt management literacy, and social capital affect the performance of MSMEs. However, the literacy variables for budgeting, and financial capital have no effect on the performance of MSMEs. Keywords : human resource competence. debt management literacy, budgeting literacy, financial capital, and social capital, MSME performance